2017
DOI: 10.25336/p6vs5k
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of Nigeria population censuses using mathematical methods

Abstract: This paper examines the adjustment of reported populations in Nigerian censuses. The ultimate objective is to provide reliable base populations which may be used to provide improved estimates of demographic parameters. Mathematical methods were applied to obtain adjusted data from the reported populations by sex and age in single years and five-year age groups in the 1963, 1991, and 2006 Nigerian censuses. Thereafter, the adjusted data were subjected to re-evaluation and used to obtain estimates of demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This is one of few studies that assessed pattern of self-management of hypertension in Nigeria, which has one of the highest burden of the chronic disease globally. Unlike the few previous studies in Nigeria, this study assessed each component of self-management among wider age-range of hypertensive patients, including young people who now constitute more than two-thirds of the nation's population 17 . Hence, though most respondents were older adults, a significant proportion were 40 years old or younger, and therefore potentially bear much of the dsease burden in the region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of few studies that assessed pattern of self-management of hypertension in Nigeria, which has one of the highest burden of the chronic disease globally. Unlike the few previous studies in Nigeria, this study assessed each component of self-management among wider age-range of hypertensive patients, including young people who now constitute more than two-thirds of the nation's population 17 . Hence, though most respondents were older adults, a significant proportion were 40 years old or younger, and therefore potentially bear much of the dsease burden in the region.…”
Section: Discussionmentioning
confidence: 99%
“…The South West region where the study was located, also has one of the highest prevalence rates and burden of disease due to hypertension in Nigeria18. This is key, considering that the study area and region is one of the most populated in Nigeria 20 , 21 , with high proportion of young people, who are potentially exposed to diverse psychosocial, occupational, environmental and other unknown risk factors of the chronic disease 22 . Therefore, local and regional health systems in developing countries need to anticipate high need for chronic disease care in the near future when these young adults may be developing complications 19 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the quality of reported age and sex data from the Nigerian population censuses are grossly defective; adjustment has been recommended for any meaningful usage of the reported census data, especially for the estimation of demographic parameters and developmental planning implementation in Nigeria (Ekanem, 1972;Nwogu, 2006;Ohaegbulem, 2015;Nwogu & Okoro, 2017). Nwogu & Okoro (2017) adjusted the reported populations in the Nigeria censuses using mathematical methods (such as the Carrier Farrag method, the Newton Halving method, and the United Nations Five-point method etc.). We observe that mathematical methods appear to have smoothed out genuine age patterns.…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“…As a result of poor vital registration records, data on adult mortality in most developing countries come from censuses and sample surveys [3,2]. Data from these two sources have been shown to be defective [4,2] [ [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%